Educação social na escola Marista Santa Marta: papel e constituição da(o) docente - Sául, Tamine Santos (2023)
The present research has the general objective of understanding how the teachers of the Final Years, at Escola Marista Santa Marta, constitute and self(trans)form themselves as social educators, based on their immersion/emersion in the / with the reality experienced. Thus, the research problem emerges: how does the teacher at Escola Marista Santa Marta constitute themselves and become a self-(trans)forming Social Educator? The permanent self(trans)formation with the social educator(s) teachers occurred through the political-epistemological proposal of the Investigativeself(trans)formative Dialogical Circles and, the understanding and interpretation of the constructs occurred through Discursive Textual Analysis combined with philosophical hermeneutics. Ten Investigative-self(trans)formative Dialogical Circles were held, in which their movements made it possible to perceive some common aspects based on the life experiences and training of these subjects. As a construct of this research, two major themes emerged: School Social Education and Self(trans)training, allowing to trace some paths of understanding for school social education. The proposition of this thesis for Escola Marista Santa Marta is the continuity of Dialogic Investigativeself(trans)training Circles, as moments of permanent self(trans)formation of its teams, as well as the construction of a PPP for and with the school and community, based on the Freirean Thematic Approach.